Apolipoprotein E genotype, cognitive performance, and dementia among diverse Latin American populations. (1st February 2022) - Llibre‐Guerra, Jorge J; Li, Jing; Llibre‐Rodriguez, Juan J; Jiménez‐Velazquez, Ivonne Z.; Acosta, Daisy M; Salas, Aquiles; Harrati, Amal; Weiss, Jordan; Liu, Mao‐Mei; Dow, William H
Abstract: Background: APOE‐ε4 allele is the most significant genetic risk factor for late‐onset Alzheimer disease (AD). The magnitude of the association between the APOE‐ε4 allele, AD, and cognitive decline has been shown to be stronger in populations of European descent relative to populations of African descent. However, these associations have been understudied in more admixed populations, including Latin American (LatAm) populations. Method: We examine the associations between APOE‐ε4, cognitive performance, and dementia prevalence among a sample of 5, 953 older adults from LatAm (Cuba, Dominican Republic [DR], Puerto Rico [PR], and Venezuela) drawn from the 10/66 Dementia Research Group study. We further examine whether global ancestry modifies these associations. Dementia diagnosis was established using the previously validated 10/66 diagnostic algorithm and DSM‐IV criteria. Results: Mean age was 72.7 in Venezuela and 75.0 years in Cuba, DR, and PR. Dementia prevalence was lower in Venezuela (6.9%) compared to the Caribbean countries (Cuba=10.6%, PR=11.7%, DR=11.8%). The prevalence of the APOE‐ε4 allele was higher in DR compared to PR, Venezuela, and Cuba. Using APOE‐ε3 allele as a reference category, presence of APOE‐ε4 was significantly associated with increased risk of dementia (OR, 2.33; 95% confidence interval [CI], 1.84, 2.81). We found that APOE‐ε4 carriers with a higher African ancestry proportion had slower cognitive decline, although this was not statistically significant. Conclusion: Although we found strong association between APOE‐ε4 and increased dementia risk; compared to previous reports in European descent populations the effect of APOE‐ε4 is attenuated in Caribbean origin populations. The possibility that African ancestry may mediate the effect of APOE‐ε4 will require further confirmation using larger samples.